Anti-reflection film, polarizing plate with Anti-reflection film, and transmissive liquid crystal display
By integrating micronized cellulose with antibacterial components into the low refractive index layer, the antireflection film provides enhanced scratch resistance and antibacterial properties, improving display durability and hygiene.
Patent Information
- Application Number
- JP2023095562
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-06-09
- Publication Date
- 2024-12-19
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing antireflection films for touch panel displays lack sufficient scratch resistance, transparency, and antibacterial properties, with methods like vapor deposition being costly and inefficient.
Incorporating micronized cellulose with antibacterial components into the low refractive index layer of the antireflection film, which includes ionic functional groups, enhances scratch resistance and maintains transparency while providing antibacterial properties.
The antireflection film achieves excellent transparency, scratch resistance, and antibacterial performance, addressing the limitations of previous technologies.
Smart Images

Figure 2024176771000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to an antireflection film, an antireflection film-coated polarizing plate, and a transmission type liquid crystal display. [Background technology]
[0002] 2. Description of the Related Art It is known that displays such as liquid crystal displays, CRT displays, EL displays, and plasma displays have an anti-reflection film provided on their surfaces to prevent degradation of visibility caused by external light being reflected on the display surface during viewing. Anti-reflective films have the ability to improve the visibility of displays by utilizing the interference and scattering of light (anti-reflective performance). In addition to anti-reflective performance, anti-reflective films may be given various other performances, such as scratch resistance to prevent scratches on displays, antistatic performance to suppress adhesion of dust, anti-soiling performance to suppress adhesion of fingerprints and dirt, and chemical resistance to prevent contamination from chemicals.
[0003] In recent years, many displays are now installed not only as image display devices but also as touch panel input devices in devices that are operated by touch, such as smartphones, laptops, car navigation systems, ATMs, and printers. Many displays as touch panel input devices are contact type. When an unspecified number of people touch a display, germs and viruses are transferred from the fingers to the display surface, and when other people touch the display, the germs and viruses are spread through the display. There is also a risk that germs and viruses may grow on the display. For this reason, frequent sterilization treatments and the like are required. Therefore, anti-reflection films are required to have antibacterial and antiviral properties (collectively referred to as antibacterial properties in this specification) as a measure against infection through the display.
[0004] It is known that a transparent coating containing a matrix and an antibacterial agent is provided to impart antibacterial properties to an antireflection film. Known antibacterial agents include organic components, metal particles such as silver having antibacterial properties, and porous particles carrying metals (Patent Document 1). Also, in order to impart antibacterial properties to an antireflection film, it is known to laminate by vapor deposition a dielectric layer containing metal ion-supported zeolite having antibacterial properties on the outermost layer of a dielectric multilayer film including one or more low refractive index dielectric layers and one or more high refractive index dielectric layers (Patent Document 2). [Prior art documents] [Patent documents]
[0005] [Patent Document 1] International Publication No. 2022 / 163397 [Patent Document 2] JP 2018-159860 A Summary of the Invention [Problem to be solved by the invention]
[0006] The display surface of a touch panel type input device is easily scratched when an input operation such as rubbing or poking the display directly with a finger or a stylus is performed. In addition, the display surface of a touch panel type input device is frequently cleaned. When the display surface is rubbed with a cloth or the like for cleaning, the display surface is easily scratched by dust, sand, and other particles adhering to the display surface. Therefore, an anti-reflection film used in such a display is required to have better scratch resistance.
[0007] However, the method of Patent Document 1 makes the transparent coating susceptible to scratches and does not provide sufficient scratch resistance. In addition, some antibacterial components are difficult to disperse in the matrix, which can cause problems with transparency. In the method of Patent Document 2, since the film is formed by vapor deposition, the cost and production speed are often inferior to wet film formation methods.
[0008] SUMMARY OF THE PRESENT DISCLOSURE An object of the present invention is to provide an anti-reflection film having excellent transparency, scratch resistance and antibacterial properties, and an anti-reflection film-coated polarizing plate and a transmission type liquid crystal display using the same. [Means for solving the problem]
[0009] As a result of intensive research, the inventors have discovered that by incorporating microfine cellulose having an antibacterial component into the low refractive index layer on the outermost surface of an antireflection film, it is possible to improve the strength of the low refractive index layer while maintaining its transparency, thereby solving the above-mentioned problems, and have thus completed the present invention.
[0010] That is, the present invention has the following aspects. [1] A hard coat layer and a low refractive index layer are provided in this order on at least one surface of a transparent substrate, 13. An anti-reflective film, wherein the low refractive index layer comprises microfibrillated cellulose having an antibacterial component and a matrix. [2] The anti-reflection film according to [1], wherein the microfibrillated cellulose has an ionic functional group. [3] The anti-reflection film according to [2], wherein the content of the ionic functional group per dry mass of the fine cellulose is 0.1 mmol / g or more and 5.0 mmol / g or less. [4] The antireflection film according to [2] or [3], wherein the ionic functional group is at least one selected from a carboxy group, a phosphate group, and a sulfo group. [5] The antireflection film according to any one of [2] to [4], wherein the microfibrillated cellulose adsorbs the antibacterial component via the ionic functional group. [6] The antireflection film according to any one of [1] to [5], comprising the hard coat layer and the low refractive index layer only on one surface of the transparent substrate. [7] A polarizing plate with an anti-reflection film, comprising a polarizing plate and the anti-reflection film according to [6], wherein the anti-reflection film is arranged with the other surface side of the transparent substrate facing the polarizing plate. [8] A transmissive liquid crystal display comprising, in order from the observer side, the anti-reflection film described in [6], a first polarizing plate, a liquid crystal cell, a second polarizing plate, and a backlight unit, wherein the anti-reflection film is arranged with the other surface side of the transparent substrate facing the first polarizing plate. Effect of the Invention
[0011] According to the present invention, it is possible to provide an antireflection film having excellent transparency, scratch resistance and antibacterial properties, and an antireflection film-coated polarizing plate and a transmission type liquid crystal display using the same. [Brief description of the drawings]
[0012] [Figure 1] FIG. 1 is a schematic cross-sectional view of an antireflection film according to an embodiment. [Diagram 2] FIG. 1 is a schematic cross-sectional view of a polarizing plate with an antireflection film according to one embodiment. [Diagram 3] FIG. 1 is a schematic cross-sectional view of a transmissive display according to an embodiment. [Figure 4] FIG. 1 is a schematic cross-sectional view of a transmissive display according to an embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0013] Hereinafter, an embodiment of the present invention will be described with reference to the drawings. However, in each of the drawings described below, the same reference numerals are used to designate corresponding parts, and the description of overlapping parts will be omitted as appropriate. In addition, this embodiment is an example of a configuration for embodying the technical idea of the present invention, and the material, shape, structure, arrangement, dimensions, etc. of each part are not specified as described below. The technical idea of the present invention can be modified in various ways within the technical scope defined by the claims described in the claims.
[0014] [Anti-reflection film] FIG. 1 shows a schematic cross-sectional view of an antireflection film according to one embodiment. As shown in FIG. 1, the antireflection film 1 of this embodiment includes a transparent substrate 11 and a hard coat layer 12 and a low refractive index layer 13 in this order on one surface of the transparent substrate 11. In this embodiment, the hard coat layer 12 and the low refractive index layer 13 are provided only on one surface of the transparent substrate 11, but the hard coat layer 12 and the low refractive index layer 13 can also be provided on the other surface of the transparent substrate 11.
[0015] <Transparent base material> The transparent substrate 11 may be any substrate that transmits light, and may be, for example, a substrate known as an anti-reflection film. A cellulose-based film such as a triacetyl cellulose film is preferable as the transparent substrate 11. The cellulose-based film has low birefringence and is excellent in optical properties such as transparency, refractive index, and dispersion, as well as in physical properties such as impact resistance, heat resistance, and durability. In addition, it can be easily dissolved or swollen by a solvent.
[0016] The transparent substrate 11 may contain various additives such as a stabilizer, an ultraviolet absorbing agent, a plasticizer, a lubricant, a colorant, an antioxidant, and a flame retardant. The thickness of the transparent substrate 11 is not particularly limited, but is preferably 10 μm or more and 200 μm or less. When the transparent substrate 11 is a cellulose-based film such as a triacetyl cellulose film, the thickness is more preferably 20 μm or more and 80 μm or less.
[0017] <Hard coat layer> An example of the hard coat layer 12 is a layer made of a cured product of a composition for forming a hard coat layer that contains an ionizing radiation curable material.
[0018] An ionizing radiation curable material is a material that can be cured by exposure to ionizing radiation. As the ionizing radiation curable material, an acrylic material is preferable in terms of transparency, processability, weather resistance, etc. The acrylic material is a material having a (meth)acryloyl group. Examples of the acrylic material include monofunctional or polyfunctional (meth)acrylate compounds such as (meth)acrylic acid esters of polyhydric alcohols, and polyfunctional urethane (meth)acrylate compounds. In addition to these, various resins having a (meth)acryloyl group (polyether resin, polyester resin, epoxy resin, alkyd resin, spiroacetal resin, polybutadiene resin, polythiol polyene resin, etc.) can be used.
[0019] In the present invention, "(meth)acrylate" refers to either one or both of "acrylate" and "methacrylate". For example, "urethane (meth)acrylate" refers to either one or both of "urethane acrylate" and "urethane methacrylate". "(meth)acrylic acid" refers to either one or both of "acrylic acid" and "methacrylic acid". "(meth)acryloyl" refers to either one or both of "acryloyl" and "methacryloyl".
[0020] Examples of the monofunctional (meth)acrylate compound include 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, t-butyl (meth)acrylate, glycidyl (meth)acrylate, acryloylmorpholine, N-vinylpyrrolidone, tetrahydrofurfuryl acrylate, cyclohexyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, and isobornyl (meth)acrylate. acrylate, isodecyl (meth)acrylate, lauryl (meth)acrylate, tridecyl (meth)acrylate, cetyl (meth)acrylate, stearyl (meth)acrylate, benzyl (meth)acrylate, 2-ethoxyethyl (meth)acrylate, 3-methoxybutyl (meth)acrylate, ethyl carbitol (meth)acrylate, phosphate (meth)acrylate, ethylene oxide modified phosphate (meth)acrylate, phenoxy (meth)acrylate, ethylene oxide modified phenoxy (meth)acrylate, propylene oxide modified fluorine Phenoxy (meth)acrylate, nonylphenol (meth)acrylate, ethylene oxide modified nonylphenol (meth)acrylate, propylene oxide modified nonylphenol (meth)acrylate, methoxydiethylene glycol (meth)acrylate, methoxypolyethylene glycol (meth)acrylate, methoxypropylene glycol (meth)acrylate, 2-(meth)acryloyloxyethyl-2-hydroxypropyl phthalate, 2-hydroxy-3-phenoxypropyl (meth)acrylate, 2-(meth)acryloyloxyethyl-2-hydroxypropyl phthalate, diethyl hydrogen phthalate, 2-(meth)acryloyloxypropyl hydrogen phthalate, 2-(meth)acryloyloxypropyl hexahydrohydrogen phthalate, 2-(meth)acryloyloxypropyl tetrahydrohydrogen phthalate, dimethylaminoethyl (meth)acrylate, trifluoroethyl (meth)acrylate, tetrafluoropropyl (meth)acrylate, hexafluoropropyl (meth)acrylate, octafluoropropyl (meth)acrylate, octafluoropropyl (meth)acrylate,Examples of the mono(meth)acrylate include adamantane derivative mono(meth)acrylates such as adamantyl acrylate having a monovalent mono(meth)acrylate derived from 2-adamantane and adamantanediol.
[0021] Examples of the polyfunctional (meth)acrylate compound include difunctional (meth)acrylate compounds and trifunctional or higher (meth)acrylate compounds. Examples of the bifunctional (meth)acrylate compound include di(meth)acrylates such as ethylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, butanediol di(meth)acrylate, hexanediol di(meth)acrylate, nonanediol di(meth)acrylate, ethoxylated hexanediol di(meth)acrylate, propoxylated hexanediol di(meth)acrylate, diethylene glycol di(meth)acrylate, polyethylene glycol di(meth)acrylate, tripropylene glycol di(meth)acrylate, polypropylene glycol di(meth)acrylate, neopentyl glycol di(meth)acrylate, ethoxylated neopentyl glycol di(meth)acrylate, tripropylene glycol di(meth)acrylate, and hydroxypivalic acid neopentyl glycol di(meth)acrylate.
[0022] Examples of the trifunctional or higher (meth)acrylate compound include tri(meth)acrylates such as trimethylolpropane tri(meth)acrylate, ethoxylated trimethylolpropane tri(meth)acrylate, propoxylated trimethylolpropane tri(meth)acrylate, tris(2-hydroxyethyl)isocyanurate tri(meth)acrylate, glycerin tri(meth)acrylate, and glycerin propylene oxide adduct triacrylate; trifunctional compounds such as pentaerythritol tri(meth)acrylate, dipentaerythritol tri(meth)acrylate, and ditrimethylolpropane tri(meth)acrylate. polyfunctional (meth)acrylate compounds having 4 or more functional groups, such as pentaerythritol tetra(meth)acrylate, ditrimethylolpropane tetra(meth)acrylate, dipentaerythritol tetra(meth)acrylate, dipentaerythritol penta(meth)acrylate, ditrimethylolpropane penta(meth)acrylate, dipentaerythritol hexa(meth)acrylate, and ditrimethylolpropane hexa(meth)acrylate; and polyfunctional (meth)acrylate compounds in which a portion of these (meth)acrylates is substituted with an alkyl group or ε-caprolactone.
[0023] The polyfunctional urethane (meth)acrylate compound can be obtained by reacting a polyhydric alcohol, a polyisocyanate, and a hydroxyl group-containing (meth)acrylate. Examples of polyfunctional urethane (meth)acrylate compounds include, but are not limited to, UA-306H, UA-306T, UA-3061, etc. manufactured by Kyoeisha Chemical Co., Ltd.; UV-1700B, UV-6300B, UV-7600B, UV-7605B, UV-7640B, UV-7650B, etc. manufactured by Nippon Synthetic Chemical Industry Co., Ltd.; U-4HA, U-6HA, UA-100H, U-6LPA, U-15HA, UA-32P, U-324A, etc. manufactured by Shin-Nakamura Chemical Co., Ltd.; Ebecryl-1290, Ebecryl-1290K, Ebecryl-5129, etc. manufactured by Daicel-UCB Ltd.; and UN-3220HA, UN-3220HB, UN-3220HC, UN-3220HS, etc. manufactured by Negami Chemical Industries, Ltd.
[0024] In order to impart electrical conductivity to the hard coat layer 12 and provide the anti-reflection film with antistatic properties, an acrylic material containing a quaternary ammonium cation-containing functional group in the molecule may be used. The quaternary ammonium cation-containing functional group is -N + X - It has a structure of a quaternary nitrogen atom (-N + ) and cation (X - ) can provide electrical conductivity to the hard coat layer 12. Examples of acrylic materials containing a quaternary ammonium cation-containing functional group in the molecule include polyfunctional or polyfunctional (meth)acrylate compounds containing a quaternary ammonium cation-containing functional group in the molecule, and polyfunctional urethane (meth)acrylate compounds containing a quaternary ammonium cation-containing functional group in the molecule. In addition to these, various resins containing a (meth)acryloyl group and a quaternary ammonium cation-containing functional group in the molecule (polyether resin, polyester resin, epoxy resin, alkyd resin, spiroacetal resin, polybutadiene resin, polythiolpolyene resin, etc.) can be used.
[0025] By using an acrylic material containing a quaternary ammonium cation-containing functional group in the molecule, the low refractive index layer 13 can be stably formed on the hard coat layer 12. The hard coat layer 12 can be made conductive by forming the hard coat layer 12 using a material having a quaternary ammonium cation-containing functional group but not having a (meth)acryloyl group and an acrylic material having no quaternary ammonium cation-containing functional group, but in this case, the material containing the quaternary ammonium cation-containing functional group may segregate on the surface. If the material containing the quaternary ammonium cation-containing functional group segregates on the surface, the coating liquid for forming the low refractive index layer may be repelled when the coating liquid for forming the low refractive index layer is applied onto the hard coat layer. In addition, the low refractive index layer 13 formed may be whitened. By using an acrylic material containing a quaternary ammonium cation-containing functional group in the molecule, the acrylic material containing a quaternary ammonium cation-containing functional group in the molecule forms a matrix, making it possible to prevent surface segregation.
[0026] The composition for forming a hard coat layer typically contains a photopolymerization initiator in addition to the ionizing radiation curable material. Examples of the photopolymerization initiator include 2,2-ethoxyacetophenone, 1-hydroxycyclohexyl phenyl ketone, dibenzoyl, benzoin, benzoin methyl ether, benzoin ethyl ether, p-chlorobenzophenone, p-methoxybenzophenone, Michler's ketone, acetophenone, 2-chlorothioxanthone, etc. These can be used alone or in combination of two or more.
[0027] The composition for forming a hard coat layer may further contain other components in addition to the ionizing radiation curable material and the photopolymerization initiator, such as a photosensitizer and a thermoplastic resin. Examples of photosensitizers include tertiary amines such as triethylamine, triethanolamine, and 2-dimethylaminoethanol, alkylphosphines such as triphenylphosphine, and thioethers such as β-thiodiglycol, etc. These can be used alone or in combination of two or more.
[0028] Examples of thermoplastic resins include cellulose derivatives such as acetyl cellulose, nitrocellulose, acetyl butyl cellulose, ethyl cellulose, and methyl cellulose, vinyl resins such as vinyl acetate and its copolymers, vinyl chloride and its copolymers, and vinylidene chloride and its copolymers, acetal resins such as polyvinyl formal and polyvinyl butyral, acrylic resins such as acrylic resins and its copolymers, methacrylic resins and its copolymers, polystyrene resins, polyamide resins, linear polyester resins, and polycarbonate resins. These may be used alone or in combination of two or more.
[0029] The thickness of the hard coat layer 12 is preferably 3 μm or more, more preferably 5 μm or more, and is preferably 10 μm or less, more preferably 7 μm or less. If the thickness is equal to or more than the lower limit, sufficient strength is obtained, and if the thickness is equal to or less than the upper limit, coating accuracy and handling are excellent. If the thickness exceeds 10 μm, the substrate may be warped, distorted, or broken due to cure shrinkage. The lower limit and the upper limit can be appropriately combined. For example, the thickness may be 3 μm or more and 10 μm or less, or 5 μm or more and 7 μm or less.
[0030] (Method of forming hard coat layer) The hard coat layer 12 can be formed, for example, by a method in which a coating film of a composition for forming a hard coat layer is formed on the transparent substrate 11 and the coating film is irradiated with ionizing radiation to cure it. The method for forming the coating film is preferably a method in which a coating liquid for forming a hard coat layer, which contains a composition for forming a hard coat layer and a liquid medium, is applied onto the transparent substrate 11 by a wet coating method, and then dried.
[0031] The coating liquid for forming a hard coat layer preferably contains, as a liquid medium, a solvent that dissolves or swells the surface of the transparent substrate 11. For example, when the transparent substrate 11 is a cellulose-based film, the coating liquid for forming a hard coat layer preferably contains a solvent that dissolves or swells the surface of the cellulose-based film. The adhesion between the transparent substrate 11 and the hard coat layer 12 can be improved by forming the hard coat layer 12 using a coating liquid containing a solvent that dissolves or swells the surface of the transparent substrate 11. In addition, the hard coat layer 12 can be formed in which the transparent substrate components and the hard coat layer components are mixed, and the obtained antireflection film is less likely to have interference unevenness.
[0032] Examples of the solvent that dissolves or swells the surface of the cellulose-based film include ethers such as dibutyl ether, dimethoxymethane, dimethoxyethane, diethoxyethane, propylene oxide, 1,4-dioxane, 1,3-dioxolane, 1,3,5-trioxane, tetrahydrofuran, anisole, and phenetole; ketones such as acetone, methyl ethyl ketone, diethyl ketone, dipropyl ketone, diisobutyl ketone, cyclopentanone, cyclohexanone, methylcyclohexanone, and methylcyclohexanone; esters such as ethyl formate, propyl formate, n-pentyl formate, methyl acetate, ethyl acetate, methyl propionate, ethyl propionate, n-pentyl acetate, and γ-butyrolactone; and cellosolves such as methyl cellosolve, cellosolve, butyl cellosolve, and cellosolve acetate. These can be used alone or in combination of two or more. Among these, at least one selected from the group consisting of methyl acetate, ethyl acetate, methyl ethyl ketone, acetylacetone, acetone, and cyclohexanone is preferable.
[0033] Examples of the wet film forming method include dip coating, spin coating, flow coating, spray coating, roll coating, gravure roll coating, air doctor coating, blade coating, wire doctor coating, knife coating, reverse coating, transfer roll coating, microgravure coating, kiss coating, cast coating, slot orifice coating, calendar coating, and die coating. Microgravure coating is particularly preferred because it can uniformly form a thin layer. When a thick layer is to be formed, die coating is also preferred.
[0034] Examples of ionizing radiation that is irradiated to cure the coating include ultraviolet light. For ultraviolet light irradiation, a high-pressure mercury lamp, a halogen lamp, a xenon lamp, a fusion lamp, etc. can be used. The ultraviolet light irradiation dose is usually 100 mJ / cm.2 More than 800mJ / cm 2 The following is the result. When the coating film is cured, heating may be performed in addition to irradiation with ionizing radiation.
[0035] <Low refractive index layer> The low refractive index layer 13 is a layer having a lower refractive index than the hard coat layer 12. By laminating the low refractive index layer 13 on the hard coat layer 12, antireflection performance is achieved. Preferably, the refractive index of the hard coat layer 12 is 1.5 to 1.7, and the refractive index of the low refractive index layer 13 is 1.3 to less than 1.5. If the refractive index of the low refractive index layer 13 is high, the difference in refractive index with the hard coat layer 12 becomes small, so it is desirable for the low refractive index layer 13 to have a low refractive index. The refractive index of each of the hard coat layer 12 and the low refractive index layer 13 is measured by the critical angle method.
[0036] The low refractive index layer 13 includes finely divided cellulose 132 having an antibacterial component 133, and a matrix 134. The matrix 134 forms a continuous phase in the low refractive index layer 13. The finely divided cellulose 132 having the antibacterial component 133 is dispersed in the matrix 134. By including the microfibrillated cellulose 132 having the antibacterial component 133 in the low refractive index layer 13, excellent scratch resistance and antibacterial properties can be imparted without impairing transparency.
[0037] Moreover, the low refractive index layer 13 of this embodiment contains low refractive index particles 131. The low refractive index particles 131 are dispersed in a matrix . The low refractive index particles 131 adjust the refractive index of the low refractive index layer 13. By including the low refractive index particles 131, the refractive index of the layer becomes lower than when the low refractive index particles 131 are not included. The low refractive index layer 13 does not necessarily have to contain the low refractive index particles 131. For example, the refractive index can also be adjusted by the material forming the matrix .
[0038] The content of the fine cellulose 132 having the antibacterial component 133 in the low refractive index layer 13 is preferably 0.1 parts by mass or more and 200 parts by mass or less, and more preferably 10 parts by mass or more and 100 parts by mass or less, relative to 100 parts by mass of the matrix 134. When the content is 0.1 parts by mass or more, the fine cellulose 132 can impart excellent scratch resistance to the low refractive index layer 13. When the content is 200 parts by mass or less, an increase in the refractive index of the low refractive index layer 13 due to the refractive index of the fine cellulose 132 can be suppressed, and the refractive index of the low refractive index layer 13 can be reduced.
[0039] The content of the low refractive index particles 131 in the low refractive index layer 13 is preferably 0.1 parts by mass or more and 500 parts by mass or less, and more preferably 10 parts by mass or more and 200 parts by mass or less, relative to 100 parts by mass of the matrix 134. When the content is 0.1 parts by mass or more, the effect of reducing the refractive index of the low refractive index layer 13 by the low refractive index particles 131 is easily obtained. Also, when the content is 500 parts by mass or less, the low refractive index particles 131 can be sufficiently fixed by the matrix 134, and the low refractive index layer 13 is easily formed.
[0040] (Low refractive index particles) The refractive index of the low refractive index particles 131 is usually lower than that of the low refractive index layer 13. The refractive index of the low refractive index particles 131 is preferably 1.4 or less, more preferably 1.35 or less. The lower limit of the refractive index is not particularly limited, but is, for example, 1.25. The refractive index of the low refractive index particles 131 is measured by the critical angle method.
[0041] The low refractive index particles 131 include particles made of a low refractive index material, particles having voids inside the particles, and the like. Examples of the low refractive index material in the particles made of a low refractive index material include LiF, MgF, 3NaF·AlF and AlF (all of which have a refractive index of 1.4), Na3AlF6 (cryolite, refractive index 1.33), etc. The particles made of a low refractive index material may or may not have voids inside the particles. Particles with voids inside have a very low refractive index because the voids can have the refractive index of air (≒1). Examples of particles with voids inside include porous particles and hollow particles. Examples of materials that make up the particles include silica.
[0042] The average particle diameter of the low refractive index particles 131 is preferably 1 nm or more and 100 nm or less. When the average particle diameter is 100 nm or less, the reflection of light due to Rayleigh scattering and the associated whitening of the low refractive index layer 13 are suppressed, and the transparency of the antireflection film tends to improve. On the other hand, when the average particle diameter is 1 nm or more, the aggregation of the low refractive index particles 131 is suppressed, and the dispersion uniformity of the low refractive index particles 131 in the low refractive index layer 13 tends to improve. The average particle size is measured by dynamic light scattering.
[0043] (Micronized cellulose with antibacterial properties) "Micronized cellulose" is cellulose that has been micronized to the point where at least one side of its structure is on the order of nanometers when dispersed in a liquid medium. Microfibrillated cellulose has high transparency due to being microfibrillated in addition to the characteristics of cellulose such as high strength, high elastic modulus, high crystallinity, and low coefficient of linear thermal expansion.
[0044] The fine cellulose 132 is preferably fibrous from the viewpoint of reinforcing the matrix 134. Fibrous fine cellulose is also called cellulose nanofiber.
[0045] The number average minor axis diameter of the fibrous fine cellulose 132 is preferably 1 nm or more and 1000 nm or less, more preferably 2 nm or more and 500 nm or less. When the number average minor axis diameter is 1 nm or more, a highly crystalline and rigid fine cellulose fiber structure can be obtained, and the strength of the low refractive index layer 13 is improved. On the other hand, when the number average minor axis diameter is 1000 nm or less, the surface smoothness of the low refractive index layer 13 is improved and the transparency of the antireflection film is not easily impaired.
[0046] The number average major axis diameter of the fibrous fine cellulose 132 is preferably 5 times or more the number average minor axis diameter. When the number average major axis diameter is 5 times or more the number average minor axis diameter, a network structure is easily formed by entanglement of the fine cellulose 132 in the matrix 134, improving the reinforcing effect. There is no particular upper limit to the number average major axis diameter, but it is, for example, 1000 times or less the number average minor axis diameter.
[0047] The number average minor axis diameter of fibrous fine cellulose is determined, for example, by measuring the minor axis diameters (minimum diameters) of 100 fibers by observation with a transmission electron microscope and an atomic force microscope, and calculating the average value. The number average major axis diameter of fibrous fine cellulose is determined, for example, by measuring the major axis diameters (maximum diameters) of 100 fibers by observation with a transmission electron microscope and an atomic force microscope, and taking the average value thereof.
[0048] The fine cellulose 132 preferably has an ionic functional group. Many antibacterial components 133 are ionic. When the fine cellulose 132 has an ionic functional group, the fine cellulose 132 can easily adsorb the antibacterial component 133. Ionic functional groups are introduced onto the surface of cellulose crystals by chemical modification.
[0049] Examples of the ionic functional group include a cationic functional group and an anionic functional group. The fine cellulose 132 may have only a cationic functional group as the ionic functional group, only an anionic functional group, or both. The ionic functional group can be appropriately selected depending on the ionicity of the antibacterial component 133. When the antibacterial component 133 contains a cationic antibacterial component, it is preferable that the antibacterial component 133 has an anionic functional group. When the antibacterial component 133 contains an anionic antibacterial component, it is preferable that the antibacterial component 133 has a cationic functional group.
[0050] As the ionic functional group, an anionic functional group is preferred because it is easy to adsorb a cationic antibacterial component. Many cationic antibacterial components are surfactants having a carbon chain, such as benzalkonium chloride, benzethonium chloride, and dialkyldimethylammonium chloride. By adsorbing such an antibacterial component to the surface of cellulose, antibacterial properties are imparted to the fine cellulose, and the dispersibility of the fine cellulose in an organic solvent is improved.
[0051] Examples of the anionic functional group include one or more groups selected from a carboxy group, a phosphate group, and a sulfo group. Among these, a carboxy group is preferred because of the ease of selective introduction onto the surface of cellulose crystals.
[0052] The content of ionic functional groups per dry mass of the fine cellulose 132 is preferably 0.1 mmol / g or more and 5.0 mmol / g or less, more preferably 0.5 mmol / g or more and 2.0 mmol / g or less. When the content of ionic functional groups is equal to or more than the lower limit, the amount of adsorption of the antibacterial component 133 increases, and antibacterial properties can be further improved. When the content of ionic functional groups is equal to or less than the upper limit, a highly crystalline rigid fiber structure can be maintained, the strength of the low refractive index layer 13 is improved, and scratch resistance can be further improved. Here, the dry mass of the fibrous cellulose 132 means the mass after the fibrous cellulose 132 is dried at 120° C. for 2 hours. The content of the ionic functional group is determined by conductometric titration.
[0053] The antibacterial component 133 is not particularly limited, but when the fine cellulose 132 has an ionic functional group, an antibacterial component that can be adsorbed by the ionic functional group is preferable. Examples of the antibacterial component 133 that can be adsorbed by an anionic functional group include cationic onium salts such as ammonium base, phosphonium base, and sulfonium base, and compounds having an antibacterial active group such as a phenylamide group or biguanide group.
[0054] The method for producing the fine cellulose 132 having the antibacterial component 133 is not particularly limited. For example, the fine cellulose 132 having a carboxy group as an ionic functional group and having an antibacterial component 133 adsorbed by the carboxy group can be produced as follows.
[0055] First, the cellulose raw material is subjected to an oxidation treatment to introduce a carboxyl group (oxidation step). The type and crystal structure of the cellulose raw material are not particularly limited. Specifically, as the raw material made of cellulose type I crystals, for example, wood-based natural cellulose or non-wood-based natural cellulose can be used. Examples of non-wood-based natural cellulose include cotton linters, bamboo, hemp, bagasse, kenaf, bacterial cellulose, sea squirt cellulose, and valonia cellulose. Examples of the raw material made of cellulose type II crystals include regenerated cellulose represented by rayon fiber and cupra fiber. In view of ease of material procurement, it is preferable to use wood-based natural cellulose as the raw material. There are no particular limitations on the wood-based natural cellulose, and for example, coniferous pulp, broadleaf pulp, waste paper pulp, and other materials that are generally used in the production of cellulose nanofibers can be used. Coniferous pulp is preferable in view of ease of purification and pulverization.
[0056] The method of oxidation is not particularly limited, and known methods can be appropriately adopted. For example, a method of reacting a cellulose raw material with monochloroacetic acid or sodium monochloroacetate in a high-concentration alkaline aqueous solution to perform carboxymethylation may be used. A method of directly reacting a carboxylic anhydride compound such as maleic acid or phthalic acid gasified in an autoclave with a cellulose raw material to introduce a carboxy group may be used. A method of oxidizing a cellulose raw material using an N-oxyl compound such as TEMPO, which has high selectivity for the oxidation of alcoholic primary carbons while maintaining the structure as much as possible under relatively mild aqueous conditions, may be used. Oxidation using an N-oxyl compound is preferred from the viewpoints of selectivity of the carboxyl group introduction site and reduction of environmental load.
[0057] Examples of the N-oxyl compound include TEMPO (2,2,6,6-tetramethylpiperidinyl-1-oxy radical), 2,2,6,6-tetramethyl-4-hydroxypiperidine-1-oxyl, 4-methoxy-2,2,6,6-tetramethylpiperidine-N-oxyl, 4-ethoxy-2,2,6,6-tetramethylpiperidine-N-oxyl, 4-acetamido-2,2,6,6-tetramethylpiperidine-N-oxyl, etc. Among these, TEMPO is preferred because of its high reactivity. The amount of the N-oxyl compound used is not particularly limited and may be a catalytic amount, and is usually about 0.01 to 5.0% by mass based on the solid content of the cellulose raw material to be oxidized.
[0058] An example of an oxidation method using an N-oxyl compound is a method in which a cellulose raw material is dispersed in water and oxidized in the presence of an N-oxyl compound. In this case, it is preferable to use a co-oxidizing agent together with the N-oxyl compound. In this case, in the reaction system, the N-oxyl compound is successively oxidized by the co-oxidizing agent to generate an oxoammonium salt, and the cellulose is oxidized by the oxoammonium salt. According to this oxidation treatment, the oxidation reaction proceeds smoothly even under mild conditions, and the introduction efficiency of the carboxyl group is improved. When the oxidation treatment is performed under mild conditions, the crystal structure of the cellulose is easily maintained.
[0059] As the co-oxidizing agent, any oxidizing agent can be used as long as it is capable of promoting the oxidation reaction, such as halogens, hypohalous acids, halo-ous acids, perhalogen acids, or their salts, halogen oxides, nitrogen oxides, peroxides, etc. Sodium hypochlorite is preferred in view of its availability and reactivity. The amount of the co-oxidant used is not particularly limited as long as it is an amount capable of promoting the oxidation reaction, and is usually about 1 to 200% by mass based on the solid content of the cellulose raw material to be oxidized.
[0060] At least one compound selected from the group consisting of bromides and iodides may be used together with the N-oxyl compound and the co-oxidizing agent. This allows the oxidation reaction to proceed smoothly, and improves the efficiency of introducing a carboxyl group. As such a compound, sodium bromide or lithium bromide is preferred, and sodium bromide is more preferred in terms of cost and stability. The amount of such a compound to be used is not particularly limited as long as it is an amount capable of promoting the oxidation reaction, and is usually about 1 to 50% by mass based on the solid content of the cellulose raw material to be oxidized.
[0061] The reaction temperature of the oxidation reaction is preferably 4°C or higher and 80°C or lower, more preferably 10°C or higher and 70°C or lower. If the reaction temperature of the oxidation reaction is lower than 4°C, the reactivity of the reagent tends to decrease and the reaction time tends to become longer. If the reaction temperature of the oxidation reaction is higher than 80°C, side reactions are promoted, which may cause the cellulose sample to depolymerize and the highly crystalline rigid structure to collapse.
[0062] The reaction time for the oxidation treatment can be appropriately set in consideration of the reaction temperature, the desired amount of carboxy groups, etc., and is not particularly limited, but is usually about 10 minutes to 5 hours.
[0063] The pH of the reaction system during the oxidation reaction is not particularly limited, but is preferably 9 to 11. When the pH is 9 or more, the reaction can proceed efficiently. When the pH exceeds 11, a side reaction may proceed, which may accelerate the decomposition of the cellulose sample. In addition, in the oxidation treatment, as the oxidation proceeds, carboxyl groups are generated, which lowers the pH in the system, so it is preferable to keep the pH of the reaction system at 9 to 11 during the oxidation treatment. As a method for keeping the pH of the reaction system at 9 to 11, for example, a method of adding an alkaline aqueous solution in response to a decrease in pH can be mentioned.
[0064] Examples of the alkaline aqueous solution include organic alkalis such as an aqueous sodium hydroxide solution, an aqueous lithium hydroxide solution, an aqueous potassium hydroxide solution, an aqueous ammonia solution, an aqueous tetramethylammonium hydroxide solution, an aqueous tetraethylammonium hydroxide solution, an aqueous tetrabutylammonium hydroxide solution, and an aqueous benzyltrimethylammonium hydroxide solution. In terms of cost, an aqueous sodium hydroxide solution is preferred.
[0065] The oxidation reaction with the N-oxyl compound can be terminated, for example, by adding an alcohol to the reaction system. In this case, it is preferable to maintain the pH of the reaction system within the above range. As the alcohol to be added, for example, low molecular weight alcohols such as methanol, ethanol, and propanol are preferred in order to quickly complete the reaction, and ethanol is particularly preferred in view of the safety of by-products generated by the reaction.
[0066] The amount of carboxyl groups introduced into the cellulose is preferably 0.1 mmol / g or more and 5.0 mmol / g or less, more preferably 0.5 mmol / g or more and 2.0 mmol / g or less. Here, when the amount of carboxyl groups is 0.1 mmol / g or more, the solvent penetrates between the cellulose microfibrils due to the osmotic pressure effect, and the cellulose is easily refined and uniformly dispersed. In addition, the amount of antibacterial components that can be imparted to the fine cellulose 132 increases, and antibacterial properties are easily expressed. On the other hand, when the amount is 5.0 mmol / g or less, the molecular weight reduction of the cellulose microfibrils due to side reactions accompanying the chemical treatment can be suppressed, a highly crystalline rigid structure can be maintained, and the effect of improving the strength can be easily obtained when the matrix 134 is incorporated therein.
[0067] After the oxidation process is terminated by stopping the oxidation reaction, the product is recovered from the reaction solution by filtration. When the reaction is stopped, the carboxyl groups introduced into the cellulose form salts with metal ions derived from the cations present in the reaction solution as counter ions. Methods for recovering cellulose after oxidation include: (a) A method in which the carboxyl group is filtered off while forming a salt, (b) A method in which an acid is added to the reaction solution to adjust the inside of the system to an acidic state, and the carboxylic acid is filtered off. (c) A method in which an organic solvent is added to cause coagulation and then the coagulation is separated by filtration; Among them, the method of recovering as a carboxylic acid (b) is preferred from the viewpoints of handling, recovery efficiency, and waste liquid treatment. In addition, in the counter ion replacement step described below, the method of recovering as a carboxylic acid (b) is preferred because it is more effective in suppressing the generation of by-products and is more efficient in replacement when there is no metal ion as a counter ion.
[0068] When the salt is recovered by filtration while still formed, the metal ion content is 5% by mass or more, whereas when the salt is recovered by filtration as a carboxylic acid, the content is 1% by mass or less. The metal ion content in the cellulose after the oxidation reaction can be determined by various analytical methods, such as EPMA using an electron probe microanalyzer or elemental analysis using X-ray fluorescence spectrometry.
[0069] The recovered cellulose can be purified by repeated washing to remove catalysts and by-products. In this case, the amount of remaining metal ions and salts can be reduced by repeatedly washing with a washing solution prepared under acidic conditions of pH 3 or less using hydrochloric acid or the like, followed by repeated washing with pure water.
[0070] Next, a cationic antibacterial component 133 is added to the suspension of the cellulose into which a carboxy group has been introduced, thereby substituting the counter ions of the carboxy groups on the cellulose surface with the cationic antibacterial component 133 (counter ion substitution step).
[0071] The amount of antibacterial component 133 added is preferably 0.8 equivalents or more and 2 equivalents or less, more preferably 1 equivalent or more and 1.8 equivalents or less, relative to the carboxyl group introduced into the cellulose. When the amount added is within the above range, counter ion exchange can be performed without adding an excessive amount of antibacterial component. Even if the amount is less than 0.8 equivalents, it is possible to disperse the cellulose to some extent, but the dispersion process requires a long time and high energy, the fiber diameter of the obtained fiber is larger than that of the present invention, and the homogeneity of the dispersion may decrease. On the other hand, if the amount exceeds 2 equivalents, there is a risk of decomposition or a decrease in affinity for the dispersion medium due to the excessive amount of antibacterial component.
[0072] By substituting the counter ions of the carboxyl groups on the surface of cellulose with the cationic antibacterial component 133, it is possible to impart antibacterial properties to the cellulose and to increase the dispersibility of the cellulose in an organic solvent. Specifically, a cellulose modified product in which the counter ions of the carboxyl groups have been substituted with the antibacterial component 133 can be subjected to dispersion treatment with less energy and in a shorter time than a cellulose modified product in which a metal ion is used as the counter ion, and the final dispersion has higher homogeneity. This is thought to be because the antibacterial component 133 has a larger ion diameter than a metal ion, and is therefore more effective at separating fine cellulose fibers from each other in the dispersion medium.
[0073] By replacing the counter ion of the carboxyl group with the antibacterial component 133, cellulose, which is inherently highly hydrophilic, can be dispersed in an organic solvent that does not contain water as fine fibers and maintain its dispersibility. The principle behind this is thought to be as follows. First, the antibacterial component 133 has an extremely high dissociation property. Furthermore, many cationic antibacterial components 133 are surfactants with carbon chains, such as benzalkonium chloride, benzethonium chloride, and dialkyldimethylammonium chloride. The hydrocarbon group of the antibacterial component 133 has a hydrophobic interaction with organic solvents. These effects cause the ions to dissociate even in organic solvents, and the ionization of the carboxyl group of the oxidized cellulose and the osmotic effect of the hydrocarbon group act, making it possible to disperse in the organic solvent.
[0074] When the cellulose having a carboxyl group introduced therein by the oxidation treatment is to be made into a dispersion, the cellulose is mixed with a dispersion medium and dispersed by the method described below (dispersion step). In this way, a dispersion of the finely divided cellulose 132 is prepared. Before the dispersion step, if necessary, the cellulose to which a carboxyl group has been introduced by the oxidation treatment is subjected to solvent substitution (solvent substitution step). Since the reaction medium in the cellulose oxidation step is water, and the cleaning agent used for washing after the reaction is mainly water, the cellulose after the oxidation treatment is recovered in a wet state containing water. Therefore, when an organic solvent other than water is contained as the dispersion medium, it is preferable to perform solvent substitution for the purpose of removing water that becomes an impurity in the dispersion medium, for the purpose of improving dispersibility by previously bringing cellulose into affinity with the dispersion medium, or for the purpose of removing insoluble components in the dispersion medium.
[0075] It is also possible to subject the oxidized cellulose to solvent substitution with an organic solvent prior to the counterion substitution step; however, as the charge repulsion of the carboxyl groups is shielded by the removal of the contained water, and as no charge repulsion occurs in the case of carboxylic acids, the cellulose may aggregate, which may adversely affect the subsequent dispersion step. Therefore, when solvent replacement is performed with an organic solvent, it is preferable to use a modified cellulose that has been subjected to counterion replacement in which the counterion of the carboxyl group of cellulose is the antibacterial component 133. This makes it possible to maintain charge repulsion due to the carboxyl group even after solvent replacement, thereby suppressing aggregation of cellulose fibers. Furthermore, the affinity with the organic solvent is improved by adsorbing the antibacterial component 133, making it easier to expel water and allowing efficient solvent replacement.
[0076] The method of solvent substitution is appropriately selected depending on the organic solvent used for solvent substitution, the properties of the antibacterial component 133 used, and other desired properties. Cellulose that has been oxidized and washed and then subjected to counterion substitution with the antibacterial component 133 and then dehydrated or dried may be used, or cellulose that has been oxidized and washed may be dehydrated or dried before the antibacterial component 133 is used. There is no limitation on the dehydration method, and a centrifuge or various filters can be appropriately selected. The drying method is not limited, and can be appropriately selected from hot air drying, infrared drying, vacuum drying, freeze drying, etc. For the purpose of suppressing aggregation accompanying drying and deterioration of cellulose due to heat, various solvents and additives can be appropriately added. The counter ion-substituted modified cellulose may be directly introduced into the organic solvent to be subjected to solvent replacement, or may be introduced into an organic solvent containing water and then the solvent may be replaced sequentially. The organic solvent used for the solvent replacement can be appropriately selected depending on the purpose as long as it does not cause aggregation or denaturation of the cellulose. In addition, the organic solvent may be the same as the dispersion medium used in the dispersion step.
[0077] By the dispersion step, the cellulose or modified cellulose having a carboxy group introduced therein is prepared into the fine cellulose 132. In other words, in this embodiment, the cellulose or modified cellulose having a carboxy group introduced therein is described as a form of cellulose prior to the stage of preparation into the fine cellulose 132.
[0078] In the dispersion treatment, when a modified cellulose is used in which the counter ion of the carboxyl group introduced into the cellulose is replaced with the antibacterial component 133, the cellulose has a high affinity for organic solvents, so that a fine cellulose dispersion can be prepared even when an organic solvent such as alcohol is used as the dispersion medium. Furthermore, if necessary, water can be added to the fine cellulose dispersion obtained by dispersing the modified cellulose in an organic solvent after the dispersion treatment. Furthermore, the affinity between the modified cellulose and the dispersion medium can be improved by prior solvent replacement, so that a homogeneous fine cellulose dispersion can be obtained without aggregation even in an organic solvent alone that does not contain water.
[0079] Examples of organic solvents used as dispersion media include methanol, ethanol, isopropyl alcohol, acetone, ethyl acetate, N,N-dimethylformamide (DMF), N,N-dimethylacetamide (DMAc), dimethylsulfoxide (DMSO), and N-methyl-2-pyrrolidone (NMP). Any one of these or a mixture of two or more of these may be used. In addition, when an inorganic alkali such as sodium hydroxide is used, it is difficult to disperse the cellulose in a solvent or mix it with the solvent after dispersion. In a fine cellulose dispersion containing metal ions from an inorganic alkali, the cellulose fibers aggregate when an organic solvent is added, causing the dispersion to become cloudy and non-uniform. Furthermore, if an organic solvent that does not contain water is used as a dispersion medium without going through a solvent replacement process, the cellulose fibers will aggregate more strongly, making it difficult to obtain a homogeneous dispersion.
[0080] The dielectric constant of the organic solvent used as the dispersion medium is preferably 15ε or more and 80ε or less at 25°C. Substances with a higher dielectric constant than water, which has a dielectric constant of 80ε (20°C), are not practical for general use. Furthermore, if the dielectric constant is lower than 15ε, the cellulose cannot maintain a dispersed state as a dispersion and will aggregate. One of the reasons for this is that the Coulomb force between the antibacterial component 133, which exists as a counter ion of the carboxyl group of cellulose, and the carboxylic acid becomes too strong, and the charge repulsion in the dispersion medium does not work.
[0081] As the method of dispersion treatment in the dispersion step, various dispersion treatments already known can be used. For example, there are homomixer treatment, mixer treatment with rotary blades, high-pressure homogenizer treatment, ultra-high-pressure homogenizer treatment, ultrasonic homogenizer treatment, nanogenizer treatment, disk-type refiner treatment, conical-type refiner treatment, double-disk-type refiner treatment, grinder treatment, ball mill treatment, kneading treatment with a twin-axis kneader, underwater facing treatment, etc. Among these, from the viewpoint of micronization efficiency, the mixer treatment with rotary blades, high-pressure homogenizer treatment, ultra-high-pressure homogenizer treatment, and ultrasonic homogenizer treatment are preferable. It is also possible to combine two or more of these treatments to perform dispersion.
[0082] The solids concentration of the cellulose in the dispersion medium in the dispersion step can be appropriately adjusted within a range that does not cause any problems in the dispersion treatment. A concentration treatment may be carried out after the dispersion treatment. There is no particular limitation on the concentration method, but a method such as centrifugation, reduced pressure, or vacuum evaporation can be appropriately selected as long as the aggregation due to drying of cellulose or the deterioration of properties due to decomposition reaction does not become a problem.
[0083] In this manner, a dispersion of cellulose (fine cellulose dispersion) is obtained in which the antibacterial component 133 is adsorbed onto the surface, the cellulose is uniformly dispersed in the organic solvent, and at least one side of the structure is micronized to the nanometer order.
[0084] (matrix) Examples of the matrix 134 include a cured product of an ionizing radiation curable material and a cured product of a thermosetting material. When the matrix 134 is a cured product of an ionizing radiation curable material or a cured product of a thermosetting material, the low refractive index layer 13 can be a layer consisting of a cured product of a composition for forming a low refractive index layer, which contains micronized cellulose 132 having an antibacterial component 133, and an ionizing radiation curable material or a thermosetting material.
[0085] As the ionizing radiation curable material forming the matrix 134, an acrylic material is preferable in terms of transparency, processability, weather resistance, etc. Examples of the acrylic material include monofunctional or polyfunctional (meth)acrylate compounds such as (meth)acrylic acid esters of polyhydric alcohols, and polyfunctional urethane (meth)acrylate compounds. In addition to these, various resins having a (meth)acryloyl group (polyether resin, polyester resin, epoxy resin, alkyd resin, spiroacetal resin, polybutadiene resin, polythiolpolyene resin, etc.) can be used.
[0086] Examples of the monofunctional (meth)acrylate compound include 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, t-butyl (meth)acrylate, glycidyl (meth)acrylate, acryloylmorpholine, N-vinylpyrrolidone, tetrahydrofurfuryl acrylate, cyclohexyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, and isobornyl (meth)acrylate. acrylate, isodecyl (meth)acrylate, lauryl (meth)acrylate, tridecyl (meth)acrylate, cetyl (meth)acrylate, stearyl (meth)acrylate, benzyl (meth)acrylate, 2-ethoxyethyl (meth)acrylate, 3-methoxybutyl (meth)acrylate, ethyl carbitol (meth)acrylate, phosphate (meth)acrylate, ethylene oxide modified phosphate (meth)acrylate, phenoxy (meth)acrylate, ethylene oxide modified phenoxy (meth)acrylate, propylene oxide modified fluorine Phenoxy (meth)acrylate, nonylphenol (meth)acrylate, ethylene oxide modified nonylphenol (meth)acrylate, propylene oxide modified nonylphenol (meth)acrylate, methoxydiethylene glycol (meth)acrylate, methoxypolyethylene glycol (meth)acrylate, methoxypropylene glycol (meth)acrylate, 2-(meth)acryloyloxyethyl-2-hydroxypropyl phthalate, 2-hydroxy-3-phenoxypropyl (meth)acrylate, 2-(meth)acryloyloxyethyl-2-hydroxypropyl phthalate, diethyl hydrogen phthalate, 2-(meth)acryloyloxypropyl hydrogen phthalate, 2-(meth)acryloyloxypropyl hexahydrohydrogen phthalate, 2-(meth)acryloyloxypropyl tetrahydrohydrogen phthalate, dimethylaminoethyl (meth)acrylate, trifluoroethyl (meth)acrylate, tetrafluoropropyl (meth)acrylate, hexafluoropropyl (meth)acrylate, octafluoropropyl (meth)acrylate, octafluoropropyl (meth)acrylate,Examples of the mono(meth)acrylate include adamantane derivative mono(meth)acrylates such as adamantyl acrylate having a monovalent mono(meth)acrylate derived from 2-adamantane and adamantanediol.
[0087] Examples of the polyfunctional (meth)acrylate compound include difunctional (meth)acrylate compounds and trifunctional or higher (meth)acrylate compounds. Examples of the bifunctional (meth)acrylate compound include di(meth)acrylates such as ethylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, butanediol di(meth)acrylate, hexanediol di(meth)acrylate, nonanediol di(meth)acrylate, ethoxylated hexanediol di(meth)acrylate, propoxylated hexanediol di(meth)acrylate, diethylene glycol di(meth)acrylate, polyethylene glycol di(meth)acrylate, tripropylene glycol di(meth)acrylate, polypropylene glycol di(meth)acrylate, neopentyl glycol di(meth)acrylate, ethoxylated neopentyl glycol di(meth)acrylate, tripropylene glycol di(meth)acrylate, and hydroxypivalic acid neopentyl glycol di(meth)acrylate.
[0088] Examples of the trifunctional or higher (meth)acrylate compound include tri(meth)acrylates such as trimethylolpropane tri(meth)acrylate, ethoxylated trimethylolpropane tri(meth)acrylate, propoxylated trimethylolpropane tri(meth)acrylate, tris(2-hydroxyethylisocyanurate tri(meth)acrylate, and glycerin tri(meth)acrylate; trifunctional (meth)acrylates such as pentaerythritol tri(meth)acrylate, dipentaerythritol tri(meth)acrylate, and ditrimethylolpropane tri(meth)acrylate. compounds; polyfunctional (meth)acrylate compounds having three or more functional groups, such as pentaerythritol tetra(meth)acrylate, ditrimethylolpropane tetra(meth)acrylate, dipentaerythritol tetra(meth)acrylate, dipentaerythritol penta(meth)acrylate, ditrimethylolpropane penta(meth)acrylate, dipentaerythritol hexa(meth)acrylate, and ditrimethylolpropane hexa(meth)acrylate; and polyfunctional (meth)acrylate compounds in which a portion of these (meth)acrylates is substituted with an alkyl group or ε-caprolactone.
[0089] Among the acrylic materials, polyfunctional urethane (meth)acrylates are preferred because they can be designed to have a desired molecular weight and molecular structure, and the physical properties of the hard coat layer 12 that is formed can be easily balanced. The polyfunctional urethane (meth)acrylate compound can be obtained by reacting a polyhydric alcohol, a polyisocyanate, and a hydroxyl group-containing (meth)acrylate. Examples of polyfunctional urethane (meth)acrylate compounds include, but are not limited to, UA-306H, UA-306T, UA-3061, etc. manufactured by Kyoeisha Chemical Co., Ltd.; UV-1700B, UV-6300B, UV-7600B, UV-7605B, UV-7640B, UV-7650B, etc. manufactured by Nippon Synthetic Chemical Industry Co., Ltd.; U-4HA, U-6HA, UA-100H, U-6LPA, U-15HA, UA-32P, U-324A, etc. manufactured by Shin-Nakamura Chemical Co., Ltd.; Ebecryl-1290, Ebecryl-1290K, Ebecryl-5129, etc. manufactured by Daicel-UCB Ltd.; and UN-3220HA, UN-3220HB, UN-3220HC, UN-3220HS, etc. manufactured by Negami Chemical Industries, Ltd.
[0090] The thermosetting material that forms the matrix 134 may be, for example, a hydrolyzate of silicon alkoxide. The hydrolysate of silicon alkoxide may be any one obtained by using silicon alkoxide as a raw material, and may be obtained, for example, by hydrolyzing silicon alkoxide with hydrochloric acid.
[0091] An example of the silicon alkoxide is a compound represented by the following formula (1). R 2 x Si(OR 1 ) 4-x ...Equation (1) In the formula, R 1 represents an alkyl group, and R 2 represents a non-reactive functional group having an alkyl group, a fluoroalkyl group or a fluoroalkylene oxide group, and x is an integer of 0 to 3. When x is an integer between 0 and 2, (4-x) R 1 When x is 2 or 3, x R 2 may be different from each other.
[0092] Examples of silicon alkoxides represented by formula (1) include tetramethoxysilane, tetraethoxysilane, tetra-iso-propoxysilane, tetra-n-propoxysilane, tetra-n-butoxysilane, tetra-sec-butoxysilane, tetra-tert-butoxysilane, tetrapentaethoxysilane, tetrapentaiso-propoxysilane, tetrapenta-n-proxisilane, tetrapenta-n-butoxysilane, tetrapenta-sec-butoxysilane, and tetrapentaethoxysilane. Examples of the silane include penta-tert-butoxysilane, methyltrimethoxysilane, methyltriethoxysilane, methyltripropoxysilane, methyltributoxysilane, dimethyldimethoxysilane, dimethyldiethoxysilane, dimethyldiethoxysilane, dimethyldimethoxysilane, dimethyldipropoxysilane, dimethyldibutoxysilane, hexyltrimethoxysilane, octadecyltrimethoxysilane, and 1H,1H,2H,2H-perfluorooctyltrimethoxysilane.
[0093] These silicon alkoxides may be used alone or in combination of two or more kinds. The silicon alkoxide is represented by the formula (1), where x is an integer of 0 to 2, and R 2 is an alkyl group (hereinafter also referred to as compound (1a)). Compound (1a) and a compound represented by the formula (1), in which x is an integer of 1 to 3, and R 2 is a non-reactive functional group having a fluoroalkyl group or a fluoroalkylene oxide group (hereinafter also referred to as compound (1b)). By further containing compound (1b), antifouling properties can be imparted to the surface of the low refractive index layer of the antireflection film, and the refractive index of the low refractive index layer 13 can be further reduced.
[0094] The low refractive index layer 13 may contain various additives as necessary. Examples of the additives include a surface conditioner, a leveling agent, a refractive index adjuster, an adhesion improver, a photopolymerization initiator, and a photosensitizer.
[0095] A photopolymerization initiator is usually used when an ionizing radiation curable material is used for the matrix 134. Examples of the photopolymerization initiator include acetophenones, benzoins, benzophenones, phosphine oxides, ketals, anthraquinones, and thioxanthones.
[0096] The low refractive index layer preferably contains a fluorine-based material, a silicone-based material, or a structure derived therefrom, which can impart antifouling properties to the surface of the low refractive index layer 13, making the antireflection film suitable for use on the surface of a display. An example of the fluorine-based material is a hydrolysate of the above-mentioned compound (1b). Examples of silicone-based materials include alkyl polyether modified silicone oil, amino modified silicone oil, and epoxy modified silicone oil.
[0097] The thickness (d) of the low refractive index layer 13 is designed so that the optical thickness (nd) obtained by multiplying the thickness (d) by the refractive index (n) of the low refractive index layer 13 is equal to 1 / 4 of the wavelength of visible light.
[0098] (Method of forming low refractive index layer) The low refractive index layer 13 can be formed, for example, by a method of forming a coating film of a composition for forming a low refractive index layer on the hard coat layer 12 and curing the coating film.
[0099] The composition for forming a low refractive index layer contains finely divided cellulose 132 having an antibacterial component 133, and an ionizing radiation curable material or a heat curable material. The composition for forming a low refractive index layer may contain low refractive index particles 131 and various additives.
[0100] A preferred method for forming the coating film is to coat a coating liquid for forming a low refractive index layer, which contains a composition for forming a low refractive index layer and a liquid medium, on the hard coat layer 12 by a wet coating method, and then dry the coating liquid. Methods for forming a low refractive index layer are divided into wet film formation methods and vacuum film formation methods, such as vacuum deposition, sputtering, and CVD, which form an anti-reflective layer in a vacuum. Vacuum film formation methods are often inferior to wet film formation methods in terms of cost and manufacturing speed. By forming a low refractive index layer by the wet film formation method, an anti-reflective film can be manufactured inexpensively.
[0101] The liquid medium for the coating liquid for forming the low refractive index layer may be an aromatic hydrocarbon such as toluene, xylene, cyclohexane, or cyclohexylbenzene; a hydrocarbon such as n-hexane; an ether such as dibutyl ether, dimethoxymethane, dimethoxyethane, diethoxyethane, propylene oxide, dioxane, dioxolane, trioxane, tetrahydrofuran, anisole, or phenetole; an ether such as methyl isobutyl ketone, methyl butyl ketone, acetone, methyl ethyl ketone, diethyl ketone, dipropyl ketone, or diisobutyl ketone. The solvent may be appropriately selected from among ketones such as cyclopentanone, cyclohexanone, methylcyclohexanone, and methylcyclohexanone; esters such as ethyl formate, propyl formate, n-pentyl formate, methyl acetate, ethyl acetate, methyl propionate, ethyl propionate, n-pentyl acetate, and γ-butyrolactone; cellosolves such as methyl cellosolve, cellosolve, butyl cellosolve, and cellosolve acetate; alcohols such as methanol, ethanol, and isopropyl alcohol; and water, taking into consideration suitability for coating.
[0102] The coating liquid for forming the low refractive index layer can be prepared, for example, by mixing a dispersion in which micronized cellulose 132 having an antibacterial component 133 is dispersed in a liquid medium with an ionizing radiation curable material or a thermosetting material. At this time, if necessary, a further liquid medium, low refractive index particles 131, and various additives may be mixed.
[0103] Examples of the wet film forming method include dip coating, spin coating, flow coating, spray coating, roll coating, gravure roll coating, air doctor coating, blade coating, wire doctor coating, knife coating, reverse coating, transfer roll coating, microgravure coating, kiss coating, cast coating, slot orifice coating, calendar coating, and die coating. Microgravure coating is particularly preferred because it can uniformly form a thin layer. When a thick layer is to be formed, die coating is also preferred.
[0104] When the composition for forming a low refractive index layer contains an ionizing radiation curable material, the coating film can be cured by irradiating the coating film with ionizing radiation. When curing the coating film, heating may be performed in addition to irradiation with ionizing radiation. Examples of ionizing radiation that is irradiated to cure the coating include ultraviolet light. For ultraviolet light irradiation, a high-pressure mercury lamp, a halogen lamp, a xenon lamp, a fusion lamp, etc. can be used. The ultraviolet light irradiation dose is usually 100 mJ / cm. 2 More than 800mJ / cm 2 The following is the result. When the composition for forming a low refractive index layer contains a thermosetting material, the coating film can be cured by heating the coating film.
[0105] [Polarizing plate with anti-reflection film] Fig. 2 is a schematic cross-sectional view of a polarizing plate with an antireflection film according to one embodiment. Note that in Fig. 2, the micronized cellulose 132 having an antibacterial component 133, the matrix 134, the low refractive index particles 131, and the like in the low refractive index layer 13 are omitted (hereinafter the same). 2, the antireflection film-attached polarizing plate 200 of this embodiment includes a polarizing plate 2 and an antireflection film 1. The antireflection film 1 is disposed such that the other surface side of the transparent substrate 11, i.e., the surface side on which the hard coat layer 12 and the low refractive index layer 13 are not laminated, faces the polarizing plate 2. The polarizing plate 2 includes a polarizing layer 23 on one surface side of a transparent substrate 21. Therefore, the polarizing layer 23 is sandwiched between the transparent substrate 21 and the transparent substrate 11 of the antireflection film 1. The anti-reflection film-attached polarizing plate 200 of this embodiment can be used as a display member or a part of an image device.
[0106] [Transmissive LCD] FIG. 3 is a schematic cross-sectional view of a transmissive liquid crystal display according to an embodiment. The transmissive liquid crystal display of FIG. 3 comprises, from the observation side (upper side in FIG. 3), a polarizing plate with an antireflection film 200, a liquid crystal cell 3, a second polarizing plate 4, and a backlight unit 5 in this order. The antireflection film-attached polarizing plate 200 is disposed with the antireflection film 1 facing the viewer. In the transmissive liquid crystal display of FIG. 3, the low refractive index layer 13 side of the antireflection film 1 serves as the display surface.
[0107] The liquid crystal cell 3 has, for example, a structure in which one transparent substrate is provided with electrodes, the other transparent substrate is provided with electrodes and a color filter, and liquid crystal is sealed between both electrodes. The second polarizing plate 4 includes a pair of transparent substrates 41 and 42, and a polarizing layer 43 sandwiched between them. The backlight unit 5 includes, for example, a light source and a light diffusion plate.
[0108] FIG. 4 shows a schematic cross-sectional view of a transmissive liquid crystal display according to another embodiment. The transmissive liquid crystal display of FIG. 4 comprises, from the observation side (upper side in FIG. 4), an antireflection film 1, a first polarizing plate 6, a liquid crystal cell 3, a second polarizing plate 4 and a backlight unit 5 in this order. The antireflection film 1 is disposed such that the other surface side of the transparent substrate 11, that is, the surface side on which the hard coat layer 12 and the low refractive index layer 13 are not laminated, faces the first polarizing plate 6. In the transmissive liquid crystal display of FIG. 4, the low refractive index layer 13 side of the antireflection film 1 serves as the display surface.
[0109] The first polarizing plate 6 includes a pair of transparent base materials 61 and 62, and a polarizing layer 63 sandwiched between them. In the transmissive LCD of Figure 3, the transparent substrate 11 of the anti-reflection film 1 also serves as the transparent substrate on the observer side of the first polarizing plate (polarizing plate 2), whereas the transmissive LCD of Figure 4 includes a transparent substrate on the observer side of the first polarizing plate in addition to the transparent substrate 11 of the anti-reflection film 1.
[0110] The transmissive liquid crystal display of the above embodiment may include other functional members. Examples of the other functional members include a diffusion film, a prism sheet, a brightness enhancement film, and a retardation film for compensating for the retardation of the liquid crystal cell or the polarizing plate, in order to effectively use the light emitted from the backlight. However, the transmissive liquid crystal display of the present invention is not limited to these. EXAMPLES
[0111] The present invention will be described in more detail below using examples, but the present invention is not limited to the following examples. "Parts" means "parts by mass".
[0112] <Example 1> The anti-reflection film according to Example 1 was produced in the following manner.
[0113] (Preparation of Coating Liquid for Forming Hard Coat Layer) A coating liquid for forming a hard coat layer was prepared by mixing 10 parts of dipentaerythritol triacrylate (DPEA), 10 parts of pentaerythritol tetraacrylate (PETA), 30 parts of urethane acrylate (product name: UA-306T, manufactured by Kyoeisha Chemical Co., Ltd.), 2.5 parts of a photopolymerization initiator (product name: Omnirad184 (Omn.184), manufactured by IGM Resins BV), 50 parts of methyl ethyl ketone (MEK) as a solvent, and 50 parts of butyl acetate.
[0114] (Preparation of Coating Liquid for Forming Low Refractive Index Layer) A finely divided cellulose dispersion was prepared by the following manufacturing method.
[0115] "Oxidation of Cellulosic Raw Materials" 10 g of bleached kraft pulp (dry mass) was left overnight in 500 mL of ion-exchanged water in a 2 L glass beaker to swell the pulp. 0.1 g of TEMPO and 1 g of sodium bromide were added and stirred to obtain a pulp suspension. Sodium hypochlorite was further added at 5 mmol / g per cellulose weight while stirring. At this time, an approximately 1 N aqueous sodium hydroxide solution was added to maintain the pH of the pulp suspension at approximately 10.5. The reaction was then continued for 2 hours, and 10 g of ethanol was added to stop the reaction, yielding oxidized cellulose in which carboxy groups had been introduced into the cellulose. The carboxy groups introduced at this time formed a salt with the sodium ion derived from the reaction reagent remaining in the reaction medium as a counter ion. Next, 0.5N hydrochloric acid was added dropwise to lower the pH to 2. The cellulose was filtered using a glass filter and further washed three times with 0.05N hydrochloric acid to convert the carboxy groups to carboxylic acids, followed by washing five times with pure water to obtain wet oxidized cellulose with a solid content of 20%. The amount of carboxy groups per dry mass of cellulose was calculated to be 1.6 mmol / g from neutralization titration with sodium hydroxide.
[0116] "Counterion substitution of carboxyl group" Water was added to the oxidized cellulose prepared above to give a solids concentration of 5% by mass to form a suspension, to which 1.2 equivalents of benzalkonium chloride (BAC) was added as an antibacterial component relative to the amount of carboxy groups in the oxidized cellulose. After stirring for 2 hours, the oxidized cellulose was filtered out using a glass filter to obtain counterion-substituted oxidized cellulose.
[0117] "Solvent replacement" The oxidized cellulose that had undergone counterion substitution as described above was subjected to solvent substitution using ethanol as the organic solvent to be used as the substitution solvent. That is, the oxidized cellulose was placed in an aqueous solution of an organic solvent in which the volume fraction of water and organic solvent was 2:1, and after stirring for 30 minutes, the oxidized cellulose was filtered and recovered using a glass filter. Next, the oxidized cellulose was similarly placed in an aqueous solution of an organic solvent in which the volume fraction of water and organic solvent was 1:1, and after stirring for 30 minutes, the oxidized cellulose was filtered and recovered, and then washed and recovered three times with the organic solvent to obtain oxidized cellulose that contained the organic solvent.
[0118] "Dispersion process" The solvent-substituted oxidized cellulose was added to ethanol, an organic solvent that serves as a dispersion medium, and treated for 1 hour using a mixer (Osaka Chemical Co., Ltd., Absolute Mill, 14,000 rpm) to obtain a micronized cellulose dispersion with a solid content of 3.0% by mass.
[0119] A coating liquid for forming a low refractive index layer was prepared by diluting 30 parts of the obtained microfine cellulose dispersion, 2.0 parts of EO-modified dipentaerythritol hexaacrylate (product name: DPEA-12, manufactured by Nippon Kayaku Co., Ltd.), 15 parts of porous silica microparticle dispersion (average particle size 60 nm, solid content 20%, solvent: methyl isobutyl ketone), 0.1 parts of photopolymerization initiator (product name: Omnirad184 (Omn.184), manufactured by IGM Resins BV), and 0.2 parts of alkyl polyether-modified silicone oil (product name: TSF4460, manufactured by GE Toshiba Silicones Co., Ltd.) with 80 parts of methyl isobutyl ketone as a solvent.
[0120] (Formation of hard coat layer) The coating solution for forming the hard coat layer was applied to one side of a triacetyl cellulose film (manufactured by Fuji Film Corporation; film thickness 60 μm) using an applicator, and then dried in an oven at 80°C for 60 seconds. After drying, the formed coating film was irradiated with an ultraviolet ray irradiation device (manufactured by Fusion UV Systems Japan, Inc.; light source H bulb) at a dose of 200 mJ / m 2 A transparent hard coat layer having a dry thickness of 5 μm was formed by irradiating the coating with ultraviolet light at 400 nm.
[0121] (Formation of low refractive index layer) The coating liquid for forming the low refractive index layer was applied onto the hard coat layer formed by the above method using an applicator, and dried for 60 seconds in an oven at 80° C. After drying, the formed coating film was irradiated with an ultraviolet ray irradiation device at a dose of 200 mJ / m 2 By irradiating the film with ultraviolet light at 400 nm, a low refractive index layer having a dry thickness of 100 nm was formed.
[0122] <Example 2> An antireflection film according to Example 2 was produced in the same manner as in Example 1, except that didecyldimethylammonium chloride (DDAC) was used instead of BAC.
[0123] <Comparative Example 1> An anti-reflection film of Comparative Example 1 was prepared in the same manner as in Example 1, except that 0.2 parts of BAC was added to the coating liquid for forming the hard coat layer, and no microfine cellulose dispersion was added to the coating liquid for forming the low refractive index layer.
[0124] <Comparative Example 2> An attempt was made to prepare an antireflection film according to Comparative Example 2 in the same manner as in Example 1, except that counter ions of the carboxyl groups of oxidized cellulose were not substituted, and the counter ions were left as sodium ions. However, oxidized cellulose in which the counter ion of the carboxyl group was sodium could not be uniformly dispersed in ethanol, and a micronized cellulose dispersion could not be prepared.
[0125] <Comparative Example 3> An antireflection film according to Comparative Example 3 was produced under the same conditions as in Example 1, except that no fine cellulose dispersion was added to the coating liquid for forming a low refractive index layer, and 0.2 parts of BAC alone was added.
[0126] Table 1 shows the materials used in preparing the coating liquids for forming the hard coat layer and the coating liquids for forming the low refractive index layer in Examples 1 and 2 and Comparative Examples 1 to 3.
[0127] The following measurements and evaluations were carried out on the antireflection films produced in Examples 1 and 2, Comparative Example 1, and Comparative Example 3. The results are shown in Table 2.
[0128] "Haze value" The haze value of the anti-reflection film was measured in accordance with JIS-K7105-1981 using an image clarity measuring device (NDH-2000, manufactured by Nippon Denshoku Industries Co., Ltd.). The lower the haze value, the more excellent the transparency.
[0129] "Average luminous reflectance" The surface of the anti-reflection film on the side of the low refractive index layer was measured for spectral reflectance at an incident angle of 5° using an automatic spectrophotometer (Hitachi U-4000). The average luminous reflectance was calculated from the obtained spectral reflectance curve. The lower the average luminous reflectance, the better the anti-reflection performance. When making the measurements, a matte black paint was applied to the surface of the triacetyl cellulose film, which is the transparent substrate, on which the low refractive index layer was not formed, to provide an anti-reflection treatment.
[0130] "Scratch resistance" The surface of the low refractive index layer of the anti-reflection film was rubbed back and forth 10 times with steel wool (#0000) at a load of 500 g, and the presence or absence of scratches was visually evaluated. Those that had no scratches were marked with a circle (○), and those that had scratches were marked with a cross (×).
[0131] "Antibacterial" According to the film adhesion method based on JIS Z 2801, a specimen sample (50 x 50 mm) and a medium (1 / 500 NB medium) were prepared, and an antibacterial test was performed using Escherichia coli (NBRC 3972) as the test bacteria. In the test, 0.4 mL of the test bacteria liquid was inoculated onto the specimen sample, and the specimen sample (40 x 40 mm anti-reflective film) was placed on top of it, and the viable bacteria count was measured after leaving it at 35 ± 1°C and a relative humidity of 90% or more for 24 hours. As a control sample, a similar test was carried out using a polyethylene film that did not contain an antibacterial agent and had no antibacterial properties. The antibacterial activity value R was calculated from the logarithm of the number of viable bacteria in the target sample after 24 hours (Ut) and the logarithm of the number of viable bacteria in the test sample after 24 hours (At) according to the formula R = Ut - At, and the antibacterial properties were evaluated. When the antibacterial activity value R was 2 or more, it was marked with a circle (〇), and when it was less than 2, it was marked with a cross (×).
[0132] [Table 1]
[0133] [Table 2]
[0134] As shown in Table 2, the antireflection films of Examples 1 and 2 were excellent in transparency, scratch resistance, and antibacterial properties. On the other hand, the antireflection film of Comparative Example 1 was poor in scratch resistance and antibacterial properties. The antireflection film of Comparative Example 3 was poor in scratch resistance. [Explanation of symbols]
[0135] 1. Anti-reflective film 11...Transparent base material 12 Hard Coat Layer 13. Low refractive index layer 131 Low refractive index particles 132 Micronized Cellulose 133...Antibacterial ingredient 134 Matrix 2 Polarizing plate (first polarizing plate) 21...Transparent base material 22...Transparent base material 23 Polarizing layer 200 ···Polarizing plate with anti-reflection film 3. Liquid crystal cell 4. Second polarizing plate 41...Transparent base material 42...Transparent base material 43 Polarizing layer 5 Backlight unit 6 First polarizing plate 61...Transparent base material 62...Transparent base material 63 Polarizing layer
Claims
1. A hard coat layer and a low refractive index layer are provided on at least one surface of a transparent substrate in this order from the transparent substrate side, 13. An anti-reflective film, wherein the low refractive index layer comprises microfibrillated cellulose having an antibacterial component and a matrix.
2. The anti-reflective film according to claim 1 , wherein the finely divided cellulose has an ionic functional group.
3. 3. The anti-reflection film according to claim 2, wherein the content of the ionic functional group per dry mass of the fine cellulose is 0.1 mmol / g or more and 5.0 mmol / g or less.
4. The anti-reflection film according to claim 2 , wherein the ionic functional group is at least one selected from the group consisting of a carboxy group, a phosphate group, and a sulfo group.
5. The anti-reflective film according to claim 2 , wherein the microfibrillated cellulose adsorbs the antibacterial component via the ionic functional group.
6. The anti-reflection film according to claim 1 , comprising the hard coat layer and the low refractive index layer only on one surface of the transparent substrate.
7. A polarizing plate with an anti-reflection film, comprising: a polarizing plate; and the anti-reflection film according to claim 6, wherein the anti-reflection film is disposed such that the other surface side of the transparent substrate faces the polarizing plate.
8. 7. A transmissive liquid crystal display comprising, in order from the observer side, the anti-reflection film according to claim 6, a first polarizing plate, a liquid crystal cell, a second polarizing plate, and a backlight unit, the anti-reflection film being arranged with the other surface side of the transparent substrate facing the first polarizing plate.
Citation Information
Patent Citations
Optical product
JP2018159860A
Particles, and substrate with transparent coating film containing said particles
WO2022163397A1
